Cardiac output as a predictor in congenital heart disease: Are we stating the obvious?. (1st May 2016) - Abualsaud, Ali O.; Lowe, Boris S.; Guo, Kenneth; Marelli, Ariane J.; Kaouache, Mohammed; Guo, Liming; Jutras, Luc; Martucci, Giuseppe; Therrien, Judith
Abstract: Background: Significant pulmonary regurgitation, declining right-sided ejection fraction, increased right ventricular (RV) volumes as well as left ventricular (LV) dysfunction have all been identified as predictors of poor outcomes in patients with congenital heart disease (CHD). The prognostic value of the cardiac output (CO) in these patients however has never been studied. Methods: All consecutive ambulatory adult patients with CHD referred for magnetic resonance imaging (MRI) at the Montreal Children's Hospital between June 2007 and May 2009 were included. Right ventricular (RV) and left ventricular (LV) variables including end diastolic and end systolic volumes (EDV, ESV respectively), ejection fractions (EF) and regurgitant volumes were obtained. Cardiac index (CI) was calculated. Patients were followed for cardiac-related hospitalizations and cardiac interventions. Results: Ninety-six patients were included. Median follow up was 3.9 ± 1.4 years. Nineteen percent of patients had a systemic CI < 2.4 l/min/m 2 . LVEDV, LVEF and RVEF were significantly diminished in the low CI group with a significant increase in RVESV and total regurgitant volume. Best predictors of low CI were LVEF (AUC = 0.74), RVEF (AUC = 0.71), total RV regurgitant volume (AUC = 0.64) and RVESV (AUC = 0.563). Low systemic CI was the best predictor of cardiac-related hospitalizations (hazard ratio 3.5, 95% confidence interval 1.5–8.5) and cardiac interventions (hazard ratio 2.2, 95% confidence interval 1.3–4.0), superior to LVEF, RVEF, total regurgitant volume and RVESV parameters. Conclusions: In patients with congenital heart disease, cardiac index is the best predictor of cardiac hospitalizations and cardiac interventions.